2017
DOI: 10.1002/pi.5311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of charge carrier transport on sulfur dioxide monitoring performance of highly porous polyaniline nanofibres

Abstract: Polyaniline nanofibres (NFs) with controlled diameters were synthesized using a template-free method, with ammonium peroxidisulfate (APS) or ferric chloride (FeCl 3 ) as oxidants. Porosity studies reveal that NFs prepared with FeCl 3 possess higher effective surface area and larger pore volume compared to NFs prepared with APS. The FeCl 3 -assisted NFs show around twofold enhanced sensing response (ca 4.5%) towards 5 ppm of SO 2 at room temperature compared to APS-assisted NFs (ca 2%). The enhancement can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…For instance, controlling conductivity and morphology of sensing material is a crucial parameter in state-of-the-art sensors. It has been revealed that materials with superior conductivity are utilized to detect reducing analytes such as NH 3 [ 11 , 42 , 69 ] and that lower conductivities are suitable for monitoring oxidizing analytes such as sulfur dioxide [ 70 , 71 , 72 ]. Hence, the desired properties of sensing materials are optimized during the synthesis process by varying operational parameters.…”
Section: Unique Properties Of Mxp-ncs For Nh 3 Sensingmentioning
confidence: 99%
“…For instance, controlling conductivity and morphology of sensing material is a crucial parameter in state-of-the-art sensors. It has been revealed that materials with superior conductivity are utilized to detect reducing analytes such as NH 3 [ 11 , 42 , 69 ] and that lower conductivities are suitable for monitoring oxidizing analytes such as sulfur dioxide [ 70 , 71 , 72 ]. Hence, the desired properties of sensing materials are optimized during the synthesis process by varying operational parameters.…”
Section: Unique Properties Of Mxp-ncs For Nh 3 Sensingmentioning
confidence: 99%
“…Further, T 90 and T R90 calculations were done for both the fabricated chemiresistors to evaluate the response and recovery time for 5 ppm of ammonia at 27°C and 50% RH (Figure 12). The 90% of the elevation curve, that is, the response time 12,13 was found to be around 271 s for both the sensors.…”
Section: Resultsmentioning
confidence: 93%
“…The sensing response of PA‐2 sensor is found to be highest for ammonia amongst all reducing and oxidizing analytes, which clearly indicated its optimal selectivity. The selectivity of PA‐2 can be ascribed to the characteristic of analyte adsorbed and sensor surface 12,13 . Further, the sensing mechanism for reducing and oxidizing analytes is opposite, which can easily be picked out by electronic circuitry 12,13 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations